Implementasi Teknologi Pompa Air Tenaga Surya di Desa Karyabaru Kecamatan Barambai Kabupaten Barito Kuala - Abdul Rozaq; Muhammad Firdaus Jauhari; Raden Kelik Hardinto (Politeknik Negeri Banjarmasin, 2019)
The research and community service program in the Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Banjarmasin (Poliban) was prepared with reference to the application of science and technology that is able to provide appropriate solutions to problems, needs, and challenges in society. While community service activities focus on supporting efforts to improve community welfare and the competitiveness of universities. Based on the 2016-2021 RPJMD vision, the South Kalimantan province's medium-term regional development mission is set for 2016-2021, one of which reads